Veritas et subtilitas: truth and subtlety in the history of philosophy : essays in memory of Burkhard Mojsisch (1944-2015) - Iremaje, T'engiz; Jeck, Udo Reinhold (Bochumer Studien zur Philosophie, 2018)
"The book provides a collection of scientific papers which are dedicated to the memory of Burkhard Mojsisch. The collection includes highly qualified papers on ancient, medieval and early modern philosophy, and demonstrates the importance of the historical research of philosophy at the beginning of the 21st century and its current trends. It documents historical aspects of important philosophical discussions of contemporaneity (e.g. in the fields of intercultural philosophy and interdisciplinary philosophy, such as philosophy of neuroscience)"--